2022
DOI: 10.1021/acs.jafc.2c03515
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sweeteners and Sweetness-Enhancing Compounds Identified in Citrus Using an Efficient Metabolomics-Based Screening Strategy

Abstract: With the high demand for a healthy diet, it is necessary and important to explore natural sweeteners used in food that enhance palatability but minimize calories. Citrus is considered a good potential source of noncaloric sweeteners, but to date, only one sweetness modulator has been found in this most common fruit crop. Herein, an efficient strategy based on an in-house database and the untargeted and targeted metabolomics analyses was proposed to screen sweeteners or sweet-enhancing compounds from citrus. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Eriodictyol and dihydroquercetin which were predicted to have a low bitter taste or no bitter taste, were also sensorially evaluated, and the results obtained showed that eriodictyol and dihydroquercetin had no bitterness at the concentrations of 0.2 mM and 2 mM, respectively. It is worth noting that eriodictyol had been reported as a sweet compound in citrus, 44 which further verified the reliability of the model results. In conclusion, the verified compounds basically agreed with the results of the model and contour plots, which further proved that the experimental results were reliable.…”
Section: Food and Function Papersupporting
confidence: 76%
“…Eriodictyol and dihydroquercetin which were predicted to have a low bitter taste or no bitter taste, were also sensorially evaluated, and the results obtained showed that eriodictyol and dihydroquercetin had no bitterness at the concentrations of 0.2 mM and 2 mM, respectively. It is worth noting that eriodictyol had been reported as a sweet compound in citrus, 44 which further verified the reliability of the model results. In conclusion, the verified compounds basically agreed with the results of the model and contour plots, which further proved that the experimental results were reliable.…”
Section: Food and Function Papersupporting
confidence: 76%
“…The characterization of nonvolatile precursors in volatile biosynthetic pathways is also under‐explored and could expand our understanding of how aromas are made and modified. Finally, the discovery of non‐sugar and nonvolatile sweetness enhancers in other fruits such as citrus (Wang et al., 2022) also begs the question of whether such compounds exist in strawberry and how they could be potentially enhanced through breeding.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Interestingly, the aglycone of NHDC, hesperetin dihydrochalcone, and the corresponding flavanone analogue hesperetin along with its regioisomer homoeriodictyol have been reported to possess taste-active properties as well. [12][13][14][15]10 NHDC is a semisynthetic compound, which is commonly produced by hydrogenation of the naturally occurring neohesperidin under alkaline conditions. 7 Through subsequent hydrolysis of the neohesperidose sugar moiety, hesperetin dihydrochalcone can be formed.…”
Section: Introductionmentioning
confidence: 99%
“…However, some flavanones and dihydrochalcones show remarkable bitter-masking or sweet-tasting properties. Naringin dihydrochalcone and, especially, neohesperidin dihydrochalcone (NHDC) are well-known taste-active flavonoids widely applied in foods. Interestingly, the aglycone of NHDC, hesperetin dihydrochalcone, and the corresponding flavanone analogue hesperetin along with its regioisomer homoeriodictyol have been reported to possess taste-active properties as well. , NHDC is a semisynthetic compound, which is commonly produced by hydrogenation of the naturally occurring neohesperidin under alkaline conditions . Through subsequent hydrolysis of the neohesperidose sugar moiety, hesperetin dihydrochalcone can be formed.…”
Section: Introductionmentioning
confidence: 99%